2011
DOI: 10.1063/1.3590718
|View full text |Cite
|
Sign up to set email alerts
|

Calculating solvation energies by means of a fluctuating charge model combined with continuum solvent model

Abstract: Continuum solvent models have shown to be very efficient for calculating solvation energy of biomolecules in solution. However, in order to produce accurate results, besides atomic radii or volumes, an appropriate set of partial charges of the molecule is needed. Here, a set of partial charges produced by a fluctuating charge model-the atom-bond electronegativity equalization method model (ABEEMσπ) fused into molecular mechanics is used to fit for the analytical continuum electrostatics model of generalized-Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 149 publications
0
8
0
Order By: Relevance
“…Wilson and Ichikawa and Torrent‐Sucarrat and coworkers pointed out that the charge transfer between atoms in a molecule is overestimated by using the polarization basis sets. Huzinaka et al, Jakalian et al, Watanabe et al, and our group have shown that the use of higher levels of basis sets overestimates the overlap between their respective basis functions belonging to two atoms in a molecule. Bayly and his coworkers pointed out that when the 6‐31G* basis set is used, the polarity of a molecule calculated by the partial charges is overestimated by 10%–15% .…”
Section: Computational Detailsmentioning
confidence: 66%
“…Wilson and Ichikawa and Torrent‐Sucarrat and coworkers pointed out that the charge transfer between atoms in a molecule is overestimated by using the polarization basis sets. Huzinaka et al, Jakalian et al, Watanabe et al, and our group have shown that the use of higher levels of basis sets overestimates the overlap between their respective basis functions belonging to two atoms in a molecule. Bayly and his coworkers pointed out that when the 6‐31G* basis set is used, the polarity of a molecule calculated by the partial charges is overestimated by 10%–15% .…”
Section: Computational Detailsmentioning
confidence: 66%
“…Atomic charges of this type are based on the concept of electronegativity. Some methods based on the electronegativity equalization principle in DFT have been developed, such as Mortier's electronegativity equalization method (EEM); the split charge equilibration (SQE) model; Rappé and Goddard's QEq; York and Yang's chemical potential equilibration (CPE); the partial equalization of orbital electronegativity proposed by Gasteiger et al and Scheraga and coworker; the methods proposed by Mullay and Abraham and coworkers; and Yang's atom‐bond electronegativity equalization method (ABEEM), among others …”
Section: Introductionmentioning
confidence: 99%
“…Based on the electronegativity equalization method (EEM) 31,32 originally developed in the context of density functional theory (DFT), 33,34 the fluctuating charge model has been applied to many systems, such as water, microporous inorganic solids, organic molecules, dense and biomolecular systems, and so on. [35][36][37][38][39][40][41][42][43] Currently, a small number of fluctuating charge models for IL compounds are available. In 2008, Siehl et al 44 applied the consistent charge equilibration (CQEq) method to guanidinium chloride IL systems.…”
Section: Introductionmentioning
confidence: 99%